Knowledge, attitude, and practice of medication therapy management: a national survey among pharmacists in Indonesia - Rendrayani, Farida; Alfian, Sofa Dewi; Wahyudin, Wawan; Puspitasari, Irma Melyani (Frontiers in Public Health, 2023)
Introduction The use of medication therapy management (MTM) is a proven method for reducing medication errors. MTM services rely heavily on pharmacists as service providers, particularly in community health centers (CHCs). Thus, understanding the knowledge, attitudes, and practices (KAP) of MTM among pharmacists in CHCs is crucial to the strategy for the implementation of MTM program in Indonesia. This study aimed to assess the level of KAP regarding MTM among pharmacists working at CHCs and its associated factors and investigate pharmacists’ perceptions of the barriers and facilitators of MTM provision in the future. Methods A cross-sectional online survey was conducted. The respondents were pharmacists working at CHCs in 28 provinces in Indonesia. Descriptive statistics were used to summarize the responses. Demographic differences were determined using Chi-square and Kruskal–Wallis tests, and associations were identified using multivariable ordinal regression for knowledge and multivariable logistic regression for attitude and practice. Barriers and facilitators were determined from codes and categories of frequency derived from pharmacists’ responses to the open-ended questions. Results Of the 1,132 pharmacists, 74.9% had a high level of knowledge, 53.6% had a positive attitude, and 57.9% had a positive practice toward MTM. Gender, practice settings, province of CHCs, years of practice, and experience in MTM services were factors associated with the KAP level. Respondents perceived that the chronic disease conditions in Indonesia, MTM service features, and current practices were facilitators of MTM provision. The lack of interprofessional collaboration, staff, pharmacist knowledge, patient cooperation, facilities/drug supply/documentation systems, stakeholder support, and patient compliance were the most common barriers to MTM implementation in the future. Conclusion Most of the pharmacists had high knowledge of MTM; however, only half had positive attitudes and practices toward MTM. Information about factors associated with the KAP level suggests that direct involvement is essential to improve pharmacists’ understanding and view of MTM. Pharmacists also perceived barriers to the MTM provision in the future, such as interprofessional and pharmacist-patient relationships. A training program is needed to improve the KAP of MTM and develop skills for collaborating with other healthcare professionals and communicating with patients.